Quality of life among colorectal cancer screening patients in Malaysia - Intan Melati Abu Bakar,; Sharifa Ezat Wan Puteh,; Halim Ismail,; Raja Affendi Raja Ali,; Muhammad Radzi Abu Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
As Malaysia is experiencing a rapid increase in the incidence of colorectal cancer (CRC), the introduction of CRC screening in Malaysia serves to improve the early CRC detection among Malaysian and its treatment outcome. The present study measured Malaysian’s perception on the quality of life (QOL) based on screened individuals in Kedah, Malaysia. The study aims to determine QOL among screened individuals based on the CRC screening modalities available in Malaysia. A cross sectional study was conducted from March 2016 to April 2017 in a public tertiary hospital and a district health clinic in the state of Kedah. Three hundred and thirty respondents aged 40 to 70 years old were asked to fill-up a self-reported health survey questionnaire comprised of 36 itemised questions (SF-36). The mean age of respondents was 58.75 ±7.53 years with 52.7% of respondents being male and 47.3% female. The majority of respondents have underlying medical illness. Mean health utility’s score in CRC screening IFOBT’s only modality was higher compare to other modalities 0.85 (ANOVA F=21.505, p<0.001). For the Physical Composite Score (PCS), IFOBT’s only modality also had a higher mean score compared to other modalities of 56.64 (ANOVA F=19.655, p<0.001) in addition to the Mental Composite Score (MCS) 56.37 (ANOVA F=12.033, p<0.001). The CRC screening via IFOBT’s only modality had better QOL in health utility, physical health and mental health compared to other modalities. Therefore, the CRC screening program is essential in preserving the QOL of Malaysian population.